Private and Public Information on the Nordic Intra-Day Electricity Market - Ewa Lazarczyk (Research Institute of Industrial Economics (IFN), 2015)
This paper is an empirical investigation of how traders react to public news in a market where there are lots of non-scheduled announcements, often arriving simultaneously. Using detailed trade information from the Nordic intra-day electricity market and GARCH models, this paper examines market participants' reaction to news about sudden production and transmission failures on the electricity grid. I divide the time of news announcement into three phases: the preannouncement period - the interval up to one hour before the hour of the public announcement of a message, the contemporaneous period - the same hour as the announcement of a message, and the post-announcement period - one hour after the hour of the announcement of a message. I find effect of news on prices in the preannouncement period, indicating that private information exists and is being used for trading on the intra-day market.
Keywords: G14; L94; 330; Private information; Public information; Non-scheduled announcements; Intra-day electricity market; Nord Pool; UMMs